Integrated liver inflammatory score predicts the therapeutic outcome of patients with hepatocellular carcinoma after transarterial chemoembolization - Yu, Mengqi; An, Tian-Zhi; Li, Jun-Xiang; Chang, De-Hua; Zhang, Zi-Shu; Xiao, Yu-Dong (Journal of vascular and interventional radiology, 2021)
Purpose - To evaluate the performance of the integrated liver inflammatory score (ILIS) in predicting survival in patients with hepatocellular carcinoma (HCC) who received transarterial chemoembolization, and to compare ILIS to other prognostic scoring systems and inflammatory indices. - Materials and Methods - This study included 192 patients with unresectable HCC who underwent transarterial chemoembolization from 3 medical centers. The potential risk factors of the patients’ overall survival (OS) were determined by multivariate Cox regression analysis. The predictive performances of ILIS in 1-, 2-, 3-, 4-, and 5-year survival were evaluated using receiver operating characteristic curves. The discriminatory power in the OS of ILIS and the other known scoring systems or inflammatory indices was determined by C-statistic. - Results - Multivariate regression analysis showed that high ILIS (P = .047), low lymphocyte count (P = .034), beyond up-to-seven criteria (P = .021), and nonresponse to the first transarterial chemoembolization session (P = .039) were risk factors for poor prognosis after transarterial chemoembolization. The predictive performances of ILIS for 1-, 2-, 3-, 4-, and 5-year survival were good, with area under the curve values of 0.627, 0.631, 0.621, 0.577, and 0.681, respectively. ILIS outperformed other standard scoring systems and inflammatory indices in predicting OS, with a C-statistic of 0.625. - Conclusions - ILIS is a powerful prognostic index for predicting the survival of patients with HCC after transarterial chemoembolization, which suggests that ILIS before treatment should be considered during the patient evaluation process.